Development and Control of a 5-Axis Reconfigurable Machine Tool - Z. M. Bi (Journal of Robotics)
The development of a hybrid reconfigurable machine tool has been introduced. The machine tool consists of a tripod-based parallel kinematic machine (PKM) module with three degrees of freedom (DOF) and a serial linear 𝑋-𝑌 table with two DOF. The PKM is installed on a gantry system which is capable of reconfiguring its position and orientation. In the design of tripod-based parallel mechanism, a passive link is used to enhance the stiffness and increase the working load. To avoid the buildup of the heat of the extensive actuation, three joints are actuated via the actuators with a constant length. The geometries of the PKM have been optimized for the best and highest accuracy. In this paper, its control system and the prototyping development are focused. An open architecture is applied, the control methodologies are developed and validated, and the corresponding software tools have been implemented for the software reconfiguration of the control system.